2009
DOI: 10.2139/ssrn.1434611
|View full text |Cite
|
Sign up to set email alerts
|

The Responsiveness of Remittances to the Oil Price: The Case of the GCC

Abstract: Any opinions expressed here are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but the institute itself takes no institutional policy positions.The Institute for the Study of Labor (IZA) in Bonn is a local and virtual international research center and a place of communication between science, politics and business. IZA is an independent nonprofit organization supported by Deutsche Post Foundation. The center is associated with the University of Bonn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…For instance, they reported that in Saudi Arabia remittance outflows uncorrelated with oil prices in recent years. Also, Naufal and Termos (2009) examined the elasticity of remittances from the GCC concerning the price of crude oil. They find that the response of remittances to changes in the price of oil is inelastic (less than 0.5).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, they reported that in Saudi Arabia remittance outflows uncorrelated with oil prices in recent years. Also, Naufal and Termos (2009) examined the elasticity of remittances from the GCC concerning the price of crude oil. They find that the response of remittances to changes in the price of oil is inelastic (less than 0.5).…”
Section: Literature Reviewmentioning
confidence: 99%